PROTOTYPE OF ADAPTIVE CONTROL SYSTEM SOFTWARE USING PERCEPTRON LEARNING ALGORITHM - Masduki Zakaria (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2010)
This aims of this research is to build and to make performance test a software prototpe of adaptive control system with perceptron learning algorithm.Needs analysis is performed to find an adaptive control system specifications are required, the result is a blue print software, after a modification of the learning algorithms are tailored to the programming language, the result is a flow chart design. Software implementation is based on the flow chart that was created by using a developed by research and development approach.The results showed that th group data in the analytical calculations with research data from a running program at every step in iteration, there was no sognificant difference between the description of data in two research groups.ub 0 sb`5P8 ( =vacancy), lost the interlayer water by being heated up to 200oC to produce a dehydrated phase, H0.54 Ti1.865 0.135O4. Above 300oC, the dehydrated phase completely transformed to TiO2(B) and anatase was obtained as pure phase at 600oC. The phase transformed as the following process: H0.54Ti1.865 0.135O4 0.5H2O à H0.54Ti1.865 0.135O4 0.25H2Oà H0.54Ti1.865 0.135O4 à TiO2(B) à TiO2-anatase. ",